Pengaruh Tipe Industri, Media Exposure, Kinerja Lingkungan, dan Leverage terhadap Pengungkapan Emisi Karbon - Putri, Theresia Berliana Calya; Hermi, Hermi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to empirically test the influence of industry type, media exposure, environmental performance, and leverage on carbon emissions disclosure. This research uses a quantitative approach with a population of energy sector companies listed on the Indonesia Stock Exchange in the 2019-2020 period. The research sample was obtained as many as 80 samples using purposive sampling technique. Secondary data was obtained from annual reports, sustainability reports and PROPER reports. Data analysis includes descriptive statistics, classical assumption test, multiple linear regression, R² test, F test, and t test. Industry type has a influence on carbon emissions disclosure, while media exposure, environmental performance, and leverage have no influence on carbon emissions disclosure. The suggestion from this research is to use wider data sources, including Issuer Performance Sites, for more complete data and expand the media exposure measurement method with content analysis from social media for a more accurate picture.